2015
DOI: 10.3177/jnsv.61.502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salmon Nasal Cartilage Proteoglycan on Plasma Glucose Concentration and Active Glucose Transport in the Small Intestine

Abstract: Summary Recently, proteoglycan was purified from the nasal cartilage of salmon. Although several physiological effects have been reported, the effect of salmon nasal cartilage proteoglycan (salmon PG) on glucose metabolism remains unclear. We studied the effect of salmon PG on rat plasma glucose levels. Oral administration of 1% salmon PG significantly attenuated the increase in portal plasma glucose levels following an oral glucose tolerance test (OGTT). Additionally 1% salmon PG delayed the increase in perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…To assess the active glucose transport, the everted sacs (3.0–4.0 cm in length) were prepared from rat jejunums following our previous method (Tsuchiya et al . ). The sacs were filled with Tyrode's solution (119 mmol/L NaCl, 2.4 mmol/L K 2 HPO 4 , 0.6 mmol/L KH 2 PO 4 , 1.2 mmol/L CaCl 2 , 1.2 mmol/L MgCl 2 , 21 mmol/L NaHCO 3 and 10 mmol/L glucose, oxygenated with 95% O 2 /5% CO 2 gas, pH 7.4).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…To assess the active glucose transport, the everted sacs (3.0–4.0 cm in length) were prepared from rat jejunums following our previous method (Tsuchiya et al . ). The sacs were filled with Tyrode's solution (119 mmol/L NaCl, 2.4 mmol/L K 2 HPO 4 , 0.6 mmol/L KH 2 PO 4 , 1.2 mmol/L CaCl 2 , 1.2 mmol/L MgCl 2 , 21 mmol/L NaHCO 3 and 10 mmol/L glucose, oxygenated with 95% O 2 /5% CO 2 gas, pH 7.4).…”
Section: Methodsmentioning
confidence: 97%
“…To measure sodium‐dependent glucose transport, the transmural potential difference (ΔPD) method was followed as described in our previous study (Tsuchiya et al . ). ΔPD was continuously measured by connecting calomel half‐cells to the mucosal and serosal solution by means of a 2% agar bridge, and was recorded using a high‐sensitivity DC chart recorder (056‐1001; HITACHI, Tokyo, Japan) (Hindmarsh et al .…”
Section: Methodsmentioning
confidence: 97%
“…In 2015, Tsuchiya et al [13] found that proteoglycans (PG) are new ingestible polysaccharide-like materials that regulate glucose metabolism [13]. PG is the major non-collagenous extracellular matrix component, particularly in cartilage and skin.…”
Section: Current Research Inmentioning
confidence: 99%
“…PG is the major non-collagenous extracellular matrix component, particularly in cartilage and skin. Although it was not food originally, PG was purified abundantly from the nasal cartilage of salmon, not only as a therapeutic agent but also as a food product [13][14][15]. Tsuchiya et al [13] found that oral administration of salmon PG decreased glucose absorption in the jejunum, thereby attenuating the increase in plasma glucose levels in rats.…”
Section: Current Research Inmentioning
confidence: 99%
See 1 more Smart Citation